A flower-like Zn3V2O8/Ag composite with enhanced visible light driven photocatalytic activity: the triple-functional roles of Ag nanoparticles. (30th April 2019) - Liu, Peng; Yi, Jianhong; Bao, Rui; Fang, Dong
Abstract : Coprecipitation, calcination and photoreduction, in a combined method, were successfully employed to fabricate a flower-like Zn3 V2 O8 (ZnVO)/nano-precipitated Ag composite powder. Abstract : Coprecipitation, calcination and photoreduction, in a combined method, were successfully employed to fabricate a flower-like Zn3 V2 O8 (ZnVO)/nano-precipitated Ag composite powder. XRD, XPS, FESEM, TEM, UV-vis and PL methods were utilized to investigate its microstructure and optical performance. Results showed that the photocatalytic performance was improved due to the expanded absorption edge in the visible light region, narrowed band gap and low recombination rate of electron–hole pairs. Theoretical calculations based on density functional theory (DFT) showed that the band-gap of ZnVO could be narrowed by the hybridization of the O 2p and Zn 3d orbitals of ZnVO–Ag and the formed silver nanoparticles were beneficial for the excitation of the valence band electrons into the conduction band. Furthermore, the electric field distribution simulated by the finite-difference time-domain (FDTD) method suggested that the separation of electron–hole pairs could be accelerated by the silver SPR effect and the Schottky barrier between silver and ZnVO. Finally, a tentative mechanism of the photodegradation properties was explored based on microstructural and photocatalytic analysis.